Why Do We Still Need Large Scale Clinical Trial: The Case of n−3 PUFA - Marchioli, Roberto; Levantesi, Giacomo (Frontiers in Physiology, 2012)
After the first reports about a protective effect on coronary heart disease (CHD) published more than 40 years ago, wide interest in the therapeutic use of n-3 polyunsaturated fatty acids (n-3 PUFA) aroused. Since then, many studies and meta-analyses have reported a significantly reduced risk of CHD and CV death due to fish and n-3 PUFA intake. Some of the overviews reported a significant reduction of risk of sudden cardiac death (SCD), all-cause death, and nonfatal CV events. On the other side, recent clinical trials had mixed findings, raising concern about the consistency of the evidence on n-3 PUFA. We critically reviewed recent large clinical trials reporting data on the antiarrhythmic effects of n-3 PUFA in different clinical settings, i.e. patients with CHD, heart failure, with implantable cardioverter defibrillator (ICD), and at risk of atrial fibrillation, in order to summarize the results which are available up to date and possibly give “substantiated” fuel to the debate on the conflicting results of n-3 PUFA.